Effect of Alginate from Chilean Lessonia Nigrescens and Mwcnts on caco3 Crystallization by Classical and Non-Classical Methods - Silva-Rojas, J; Silva-Rojas, J (Multidisciplinary Digital Publishing Institute (MDPI), 2018)
In our crystallization experiments, the influence of alginate from Chilean Lessonia nigrescens and functionalized multi-walled carbon nanotubes (MWCNTs) was tested through electrocrystallization (EC) and gas diffusion (GD) methods on the crystal growth of calcium carbonate (CaCO3) and their possible stabilization of proto-structures in amorphous CaCO3 (ACC) state through pre-nucleation clusters (PNC) essays with automatic potentiometric titrations were performed. CaCO3 crystals obtained in the in vitro above-mentioned crystallization systems were characterized by scanning electron microscope (SEM), energy-dispersive X-ray spectrometry (EDS) and powder X-ray diffractometer (XRD). Our experimental findings showed that ALG and functionalized MWCNTs stabilized truncated and agglomerated vaterite-like particles through GD and EC methods. While, on the other hand, we obtained qualitative information about induction or inhibition of CaCO3 nucleation that was provided by potentiometric titrations. © 2018 by the authors. Licensee MDPI, Basel, Switzerland.